The relationship between maternal psychopathology and maternal-fetal attachment: a cross-sectional study from the Czech Republic - Hana Němcová; Marie Kuklová; Kristýna Hrdličková; Anna Horáková; Antonin Sebela (BMC Psychology)
Abstract Background Maternal-fetal attachment might be associated with maternal mental health issues, but previous results have been inconsistent, particularly regarding prenatal anxiety. We compared maternal-fetal attachment between pregnant women with and without symptoms of antenatal depression and anxiety. Additionally, we examined the relationships between prenatal depressive and anxiety symptoms, psychosocial stress, and maternal-fetal attachment. Methods We conducted a cross-sectional study involving a sample of 2,233 pregnant women. The data were collected between March 2021 and March 2023 at outpatient clinics in the Czech Republic. We used self-report questionnaires to assess symptoms of prenatal depression (Edinburgh Postnatal Depression Scale, EPDS), anxiety (Perinatal Anxiety Screening Scale, PASS), psychosocial stress (Prenatal Psychosocial Profile, PPP), and maternal-fetal attachment (Prenatal Attachment Inventory – Revised, PAI-R). Results Women without symptoms of antenatal depression had higher total scores on the PAI-R (U = 336,357; p = .013) and on the PAI-R Interaction subscale (U = 322,913; p < .001), suggesting a higher quality of maternal-fetal attachment than women with symptoms. No other significant associations were found between antenatal depression, anxiety and the PAI-R subscales scores. Conclusions Our results suggest that women experiencing increased depressive, but not anxiety, symptoms in pregnancy, have a poorer quality of attachment to their child, although the effect size is small. Consequently, treating prenatal depression in women could have a positive effect on maternal-fetal attachment.